Development of 2G and 3G spectrum management tool for spectrum utilisation in Malaysia using open source software - Mohamad Afif bin Saman (Kulliyyah of Engineering, International Islamic University Malaysia, 2015)
Mobile communication is a lucrative technology that is constantly changing. Technologies, like 4G network, tablet computer and smartphone, attract new subscribers and increase the number of cellular network users. Subsequently, this increases the demand for spectrum access. Due to scarce nature of radio frequency spectrum, a spectrum management software is needed to cater to this demand. The premium spectrum management software are expensive and rigid. They need constant updates from developers and will be costly in the long run. This research aims to develop a spectrum management tool for spectrum utilisation in Malaysia using open-source resources. The proposed tool is developed by following the evolutionary software process model, particularly spiral model. The geographical information system (GIS) framework is provided by Quantum GIS (QGIS) while PostgreSQL has been chosen as the database management system. The proposed tool is capable of displaying base station (BS) spectrum coverage area on the map as well as identifying interferences. It is built in a form of QGIS' plugin and written in PyQT programming language. The proposed tool is called Malaysia Spectrum Management Tool (Malspectrumt). It is only focused on Global System for Mobile Communications (GSM) and Universal Mobile Telecommunications System (UMTS) networks. The propagation distance of the coverage area is estimated using the existing path loss models, which are Hata model for GSM900 networks and Cost-231 Hata model for GSM1800 and UMTS2100 networks. It also implements the single knife-edge modelling technique to estimate diffraction loss. Malspectrumt can also identify co-channel interference and adjacent cell interference according to reuse distance and adjacent distance rules by utilising the rules and regulations set by Malaysia Communication and Multimedia Commission (MCMC). Malspectrumt performance is compared with commercial software, CloudRF. Path loss is estimated in both tools for two BS and it shows variation of values between both results. The path loss differences between both tools are 8.45% in the first BS and 6.13% for the second BS. The average path loss difference is 7.29%. Malspectrumt is a cost effective spectrum management tool for managing existing BS as well as planning new BS in GSM and UMTS networks.